Research and practical issues of enterprise information systems : 11th IFIP WG 8.9 Working Conference, CONFENIS 2017, Shanghai, China, October 18-20, 2017 : revised selected papers /: 11th IFIP WG 8.9 Working Conference, CONFENIS 2017, Shanghai, China, October 18-20, 2017 : revised selected papers. ([2018]) - Unknown
No abstract available